Validated RP-HPLC Method for Simultaneous Estimation of Tadalafil and Macitentan in Bulk and Dosage Forms - Sahoo, Biswa Mohan; Rao, Pallepogu Venkateswara; Rao, Naidu Srinivasa; Lakshmi, Kopuri Bhagya; Babu, Nayaka Raghavendra; Panda, Debabrata; Brahma, Chandan Kumar (Current Spectroscopy and Chromatography, 2025)
IntroductionReverse-phase high-performance liquid chromatography is a simple, quick, accurate, sensitive, and reproducible technique for quantitatively analyzing Tadalafil and Macitentan in pharmaceutical dosage form. This method is novel as it allows for the simultaneous quantification of both Tadalafil and Macitentan in a single run, which is not widely reported in existing literature.MethodsWaters Alliance-e2695 was used to perform the chromatographic separation of Tadalafil and Macitentan using an Agilent Eclipse XDB C18 (150 x 4.6 mm, 3.5 µ) column and a mobile phase that contained acetonitrile: 0.1% TFA in a 50:50% v/v ratio. At room temperature, the flow rate was found to be 1.0 ml/min, and a photodiode array detector was used to monitor the absorption at 301 nm.ResultsFor Tadalafil and Macitentan, the theoretical plate count was not less than 2000, and the tailing factor should not exceed 2. All measurements have a percentage relative standard deviation of peak areas that is consistently smaller than 2.DiscussionThe suggested approach was validated in compliance with ICH Q2 (R1) regulations. This method was deemed simple, cost-effective, accurate, precise, and reliable for quantitative analysis of the stability study of Tadalafil and Macitentan. The novelty of this work mainly depends on the use of specific mobile phase composition, pH, column type, or detection wavelength that achieves excellent separation and peak resolution within a shorter run time.ConclusionThis study shows excellent sensitivity with low LOD/LOQ values, and superior efficiency through rapid analysis, good resolution, and robustness, making it suitable for routine quality control and pharmaceutical analysis.
Keywords: tadalafil